Enhanced Recovery after Colorectal Surgery: 1st Year Experience in a Safety-Net Hospital - Stephanie D. Talutis; Uma R. Phatak; Angela H. Kuhnen; Pamela Rosenkranz; David McAneny; Jason F. Hall (World Journal of Colorectal Surgery)
Background: Enhanced recovery after surgery (ERAS) is a multidisciplinary pathway of perioperative patient care. Objective: To evaluate the effect of an ERAS program on length-of-stay (LOS) among elective colorectal surgery patients at a safety-net hospital. Design: Retrospective chart review Setting: 500+ bed in a safety-net hospital. Patients and Methods: Retrospective review of elective colorectal surgery patients comparing those participating in an ERAS protocol to historical-control (HC) patients from the preceding year. Main Outcome Measures: The primary outcome was LOS. Secondary outcomes of interest included opioid utilization, fluid balance throughout the hospital stay, return of bowel function, 30-day complications emergency department visits, and readmissions. Sample Size: 193. Results: ERAS (n = 94) and HC groups (n = 99) were similar with regards to demographics and operations performed. ERAS patients had a longer operating room (OR) time (P = 0.010), however, OR fluid rates were lower for ERAS patients (P < 0.001) with more neutral fluid balance at discharge (closer to 0) (P = 0.006). ERAS patients received fewer opioids in the OR (P < 0.001) and throughout the hospital stay (P = 0.043). Median LOS was 4 days for both groups (P = 0.141) and no difference in 30-day emergency department (ED) visits, readmission, or complications. Conclusions: Benefits of ERAS may not be immediately evident post-implementation. Further study is needed regarding the maintenance of ERAS interventions over time and the impact on patient outcomes. Limitations: Single-center retrospective nature and surgeon turnover during this period. Conflict of Interest: None.